Englishpreneurship Program sebagai Upaya Pembelajaran Integeratif di Tingkat Sekolah Dasar - Tri Kristianti; Ar Ruhimat, Imroati Istibsyaroh; Firdaus, Rizalnur (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Continuous and impactful education is considered essential for the creation of the 2045 Golden Generation focused on quality education as one of the main pillars alongside economic equality and development. Educators with integrity and adequate competence in their respective fields and expertise are expected to produce a generation with outstanding potential, and capable of enhancing Indonesia's reputation on the international stage. The mismatch between competencies and the demands of Human Resources (HR) needs can significantly affect the quality of teaching. This Community Service Program is focused on achieving maximum results for students by enhancing the quality of educators to meet the Learning Achievement standards in the Independent Curriculum for English, Entrepreneurship, and Project Creative subjects through a training program titled